2015
DOI: 10.5293/ijfms.2015.8.4.304
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of slit wall effect on the Taylor vortex flow with radial temperature gradient

Abstract: Numerical simulation was applied to investigate the Taylor vortex flow inside the concentric cylinders with a constant radial temperature gradient. The reliability of numerical simulation method was verified by the experimental results of PIV. The radial velocity and temperature distribution in plain and 12-slit model at different axial locations were compared, and the heat flux distributions along the inner cylinder wall at different work conditions were obtained. In the plain model, the average surface heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Only the velocity distribution of limited area can be obtained by particle image velocimetry(PIV) experimental measurements, and in addition, the temperature distribution and its effect to the flow structure in the gap are hard to obtain by experimental methods. Based on the investigation of the slit wall effect on Taylor vortex flow and wavy vortex flow [10,11], we studied a constant temperature gradient and slit number effect on Taylor vortex flow, which was rarely studied by numerical simulation, by PIV (TSI INCORPORATED, Shoreview, MN, USA) measurements and numerical simulation. By comparing the results of four different models, the characteristics of the vortex flow in the annulus gap and the slit number effect on the heat transfer process were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Only the velocity distribution of limited area can be obtained by particle image velocimetry(PIV) experimental measurements, and in addition, the temperature distribution and its effect to the flow structure in the gap are hard to obtain by experimental methods. Based on the investigation of the slit wall effect on Taylor vortex flow and wavy vortex flow [10,11], we studied a constant temperature gradient and slit number effect on Taylor vortex flow, which was rarely studied by numerical simulation, by PIV (TSI INCORPORATED, Shoreview, MN, USA) measurements and numerical simulation. By comparing the results of four different models, the characteristics of the vortex flow in the annulus gap and the slit number effect on the heat transfer process were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [8] studied Taylor-Couette system with different numbers of slits in the outer cylinder by using DPIV method and found that a larger number of axial slits accelerated the transition process flow wavy vortex flow to turbulent Taylor vortex flow 2 Advances in Mechanical Engineering but have no effect on the transition before wavy vortex flow. Liu et al [9] studied the slit wall effect on flow stability in Taylor vortex flow regime and found that the vortex flow expanded into the slit wall; the intensity of the vorticity and the radial velocity increased in slit model. Hayase et al [10] studied the heat transfer between rotating coaxial cylinders with periodically embedded cavities and found the flow in a cavity interacts with Taylor vortices in the annular space to enhance heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the flow field measured by DPIV in their study was limited; because of the limitation of measuring field, the slit number effect on the vortex size cannot be obtained precisely. In our study, based on the investigation of slit wall effect on Taylor vortex flow [9], we studied the wavy vortex flow in detail by PIV measurement and CFD calculation. By comparing the results in three different models, the slit wall effect on the stability of wavy vortex flow was obtained.…”
Section: Introductionmentioning
confidence: 99%